The way of the Platonic Socrates - Ewegen, S. Montgomery (Studies in Continental thought., 2020)
"Who is Socrates? While most readers know him as the central figure in Plato's work, he is hard to characterize. In this book, S. Montgomery Ewegen opens this long-standing and difficult question once again. Reading Socrates against a number of Platonic texts, Ewegen sets out to understand the way of Socrates. Taking on the nuances and contours of the Socrates that emerges from the dramatic and philosophical contexts of Plato's works, Ewegen considers questions of withdrawal, retreat, powerlessness, poverty, concealment, and release and how they construct a new view of Socrates. For Ewegen, Socrates is a powerful but strange and uncanny figure. Ewegen's withdrawn Socrates forever evades rigid interpretation and must instead remain a deep and insoluble question"--